Strain-, Sex-, and Time-Dependent Antidepressant-like Effects of Cannabidiol - Gabriela P. Silote; Michelle C. Gatto; Amanda Eskelund; Francisco S. Guimarães; Gregers Wegener; Sâmia R. L. Joca (MDPI AG, 2021)
Cannabidiol (CBD) is a non-intoxicating compound extracted from Cannabis sativa, showing antidepressant-like effects in different rodent models. However, inconsistent results have been described depending on the species and the strain used to assess depressive-like behavior. Moreover, only a few studies investigated the effect of CBD in female rodents. Therefore, we aimed to (i) investigate the effects of CBD in two different strains of mice (Swiss and C57BL/6) and a rat model of depression based on selective breeding (Flinders Sensitive and Resistant Lines, FSL and FRL) subjected to tests predictive of antidepressant-like effects and (ii) investigate the influence of sex in the effects of CBD in both mice and rats. CBD induced an antidepressant-like effect in male Swiss but not in female Swiss or C57BL/6 mice in the tail suspension test (TST). In male FSL rats, CBD produced an antidepressant-like effect 1 h post injection. However, in female FSL, CBD induced a bimodal effect, increasing the immobility time at 1 h and decreasing it at 2 h. In conclusion, strain, sex, and administration time affect CBD's behavioral response to rodents exposed to tests predictive of antidepressant effects.